2021
DOI: 10.1097/bot.0000000000002095
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the Acute Management of Open Fracture Treatment? Part 2

Abstract: Introduction: In the first installment of this two-part series, we explored the history of open fracture treatment focusing primarily on bacteriology and antibiotic selection/stewardship. In this follow-up segment, we will analyze and summarize the other aspects of open fracture care such as time to debridement, pulsatile lavage, and open wound management (including time to closure)-finishing with summative statements and recommendations based on the current most up-to-date literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…The wounds in type III fractures have thus been managed by delayed wound closure until several days post-injury to allow drainage of any slowly accumulating infectious materials 34 , 35 . Naturally, the profiles of the causative organisms differ, with a higher proportion of Gram-negative species being associated with wounds closed in a delayed fashion 7 . Jenkinson et al clearly demonstrated that Gram-negative pathogens increased more in a delayed wound closure group compared with a primary closure group, even for open fractures with the same severity 35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The wounds in type III fractures have thus been managed by delayed wound closure until several days post-injury to allow drainage of any slowly accumulating infectious materials 34 , 35 . Naturally, the profiles of the causative organisms differ, with a higher proportion of Gram-negative species being associated with wounds closed in a delayed fashion 7 . Jenkinson et al clearly demonstrated that Gram-negative pathogens increased more in a delayed wound closure group compared with a primary closure group, even for open fractures with the same severity 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Early intravenous administration of prophylactic antibiotics in open fractures is currently the standard of care for prevention of surgical site infection (SSI) 1 7 . Antibiotics should be initiated as soon as possible after injury 8 , 9 , and specifically within 3 h at the latest 3 , 7 , 9 , 10 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [40] found NPWT was associated with reduced surgical site infections in meta-analysis of 45 randomized-control trials compared with soft dressings. However, the WOLFF study, a multicenter randomized trial in patients with severe open lower limb fractures, did not identify differences in the rate of infection or self-rated disability compared to standard dressings [41] . Recent literature comparing NPWT to antibiotic bead pouches suggests that NPWT may be overutilized, provide inferior results, and cost more than antibiotic bead pouches in the management of open fractures pending soft tissue reconstruction [42] .…”
Section: Early Intervention To Prevent Infectionmentioning
confidence: 98%